Corruption, Natural Capital and Economic Development: A Dynamic GMM Analysis - Ang, Joshua; Patalinghug, Jason (Review of Economic Analysis, 2025)
Using a dynamic panel dataset of 150 countries for the period of 2006-2018 and a two-step system GMM estimation model, this paper shows that natural resources have a positive effect on economic development while holding corruption constant. Our findings support the notion that natural resources have a positive effect on the economy of a nation. When a country has less corruption, it improves the appropriation of economic gains from natural resources which serves as natural capital that would drive further capital accumulation and further development. We also find that physical capital, human capital, and freedom from corruption show strong positive effects on economic development, controlling for other economic and institutional variables.
Keywords: Corruption; Dynamic Panel Study; Econometrics; Economic Development; Economics; Human Capital; Language change; Natural Resources; Physical Capital; dept.eco

Do trade barriers and financial freedom matter in becoming a rich country? - Ang, Joshua; Patalinghug, Jason (Journal of Business and Economic Studies, 2026)
A lot has been written on the impact of economic freedom and its components on economic growth. This paper focuses on financial freedom, which is one aspect of economic freedom. Financial freedom measures how deeply the government is involved in a nation’s financial industry and how that industry is open to foreign competition. The aim of this study is to measure the effect of financial freedom and other factors on gross domestic product (GDP) per capita. We estimate a model using panel data of 184 countries from 2012 to 2019. Our empirical estimations show that financial freedom positively affects per capita GDP, while tariff rates, corporate tax rates, unemployment, and inflation negatively affect per capita GDP.
Keywords: Economic freedom; Financial analysis; Government (linguistics); Gross domestic product; Index of Economic Freedom; Inflation (cosmology); Panel data; Per capita; Tariff; dept.eco

The Effect of Property Rights on GDP per Capita - Ang, Joshua Ping; Patalinghug, Jason C. (The Empirical Economics Letters, 2020)
Keywords: dept.eco; peer-reviewed

COVID-19: effectiveness of socioeconomic factors in containing the spread and mortality - Ang, Joshua Ping; Dong, Fang; Patalinghug, Jason (International Review of Applied Economics, 2021)
This paper presents a study on 80 countries that evaluates the socioeconomic factors in containing the spread and mortality of COVID-19. Our results show that the long-term social factors such as lower personal freedom, better education in science, and past coronavirus outbreak experience are more effective than the economic factors such as higher healthcare-associated factors per 1000 population and larger GDP. However, using GDP per capita as the instrumental variable, we also find that the richer countries with a high degree of personal freedom have a higher number of infection or death cases per million population because they would be less likely to adhere to and implement the policy of the movement restrictions to restrict their access to goods and services. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
7 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85097015963
Keywords: COVID-19; Coronavirus; Gross Domestic Product; dept.eco; disease control; disease spread; epidemic; global perspective; mortality; pandemic; peer-reviewed; regression analysis; socioeconomic conditions